2013
DOI: 10.4236/fmar.2013.13008
|View full text |Cite
|
Sign up to set email alerts
|

Medicolegal autopsies in children: Experience of a department of Legal Medicine in Brazil

Abstract: Purposes: The purpose of this study was to determine the pattern of mortality in children's Federal District. Knowledge of the epidemiology of injuries is essential for planning, implementation and evaluation of preventive measures. Methods: We analyzed the forensic examination documents of all children under 12 years sent to the IML-DF, during 2010. The data analyzed included age, gender, cause of death (i.e. natural or external), mechanism of death (traffic accident, asphyxia, firearm injuries, poisoning, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This was the same as in the study by Fraga et al [1] Some studies [7,11] indicated a relatively larger proportion of male descendants, with a male:female ratio of 2.3:1 and 2.0:1, respectively. In other studies, [8,9] the ratio was less, with proportionately more female admissions, i.e. 1.4:1 and 1.2:1, respectively.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This was the same as in the study by Fraga et al [1] Some studies [7,11] indicated a relatively larger proportion of male descendants, with a male:female ratio of 2.3:1 and 2.0:1, respectively. In other studies, [8,9] the ratio was less, with proportionately more female admissions, i.e. 1.4:1 and 1.2:1, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…[1,7,11] Firearm-related deaths accounted for 6% of cases in the PMLL, Beyaztas et al [11] and Okoye and Okoye [7] studies, but for 16% of cases in the Fraga et al [1] study. In the study by Modelli et al, [8] only two gunshot-related deaths were reported in a 1-year study in children <12 years. SA has strict legislation pertaining to firearm ownership and use and on storage in appropriate gun safes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation